2020
DOI: 10.1167/tvst.9.8.8
|View full text |Cite
|
Sign up to set email alerts
|

Recognizing Atrophy and Mixed-Type Neovascularization in Age-Related Macular Degeneration Via Clinicopathologic Correlation

Abstract: Recognizing atrophy and mixed-type neovascularization in age-related macular degeneration via clinicopathologic correlation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(7 citation statements)
references
References 48 publications
(74 reference statements)
1
6
0
Order By: Relevance
“… 7 , 62 This topographic difference in GA expansion rate and GA distribution suggests that GA onset may be driven by different biological processes from GA expansion. Previous histological studies have suggested that GA lesions typically begin over drusen, 63 65 consistent with the similar topographic variation between the soft drusen height53 and the percentage area affected by GA in our study. In comparison, GA expansion is unlikely to be driven by drusen, as the atrophic lesions are commonly not surrounded by drusen.…”
Section: Discussionsupporting
confidence: 92%
“… 7 , 62 This topographic difference in GA expansion rate and GA distribution suggests that GA onset may be driven by different biological processes from GA expansion. Previous histological studies have suggested that GA lesions typically begin over drusen, 63 65 consistent with the similar topographic variation between the soft drusen height53 and the percentage area affected by GA in our study. In comparison, GA expansion is unlikely to be driven by drusen, as the atrophic lesions are commonly not surrounded by drusen.…”
Section: Discussionsupporting
confidence: 92%
“…Finally, we want to emphasize our belief that atrophy embedded within MNV, most likely arising from a pre-existing MNV, is of a different etiology and character than that of GA that independently developed, 2 , 3 and, consequently, that the subjects of our study may not be directly comparable to those of the study by Pfau et al 4 …”
mentioning
confidence: 77%
“…Advanced stages of the disease can be subclassified into non-neovascular (or dry) and neovascular (or wet) AMD. Both forms of advanced-stage AMD are accompanied by loss of photoreceptors and geographic atrophy (GA), but neovascular AMD (nAMD) is distinguished by presence of pathological angiogenesis in the macula, or macular neovascularization (MNV) [ 41 , 42 ]. According to the anatomic location and origination of the new vessels, MNV can be classified into three major types.…”
Section: Introductionmentioning
confidence: 99%
“…According to the anatomic location and origination of the new vessels, MNV can be classified into three major types. Type 1 and Type 2 MNV originate from the choroid and proliferate under the RPE (Type 1) or breaks through the RPE to reach subretinal space (Type 2), while Type 3 MNV originates from the retina and grows toward the RPE [ 41 ]. Regardless of the type of the MNV, these malformed vessels lack appropriate pericyte coverage and tight junctions between endothelial cells and are therefore prone to leakage or rupture.…”
Section: Introductionmentioning
confidence: 99%